The Retail City in Greater Birmingham - The changing face of urban retail districts as a result of retail-led regeneration and containment policy - Hermanus Geyer Jr (European Regional Science Association (ERSA), 2011)
The paper critically reviews retail-led regeneration and retail containment polices and their effects on the urban retail in the UK by analysing the effect that retail-led mega-schemes regeneration projects have on the economic growth of inner cities. There is significant controversy whether mega-schemes in retail-led regeneration initiatives contribute to the growth of local economies or whether it leads to the pitch shifting and marginalisation of local retail. The research focuses on two neighbouring strategies in Birmingham and Solihull to determine differences in the application of retail-led regeneration in inner city and peripheral locations. Birmingham's Bullring centre and Solihull's Touchstone centre was researched using quantitative data on the growth of the retail sector in Birmingham and supplemented using interviews with key actors. The paper critically analyses whether retail-led mega-schemes have a net positive effect on the economic revitalisation of the deteriorating inner cities. The results of the research indicate that the retail-led regeneration initiative brought about a dual economy with a global inner core of national retail and the outer core of marginalised local retail. The economic motive of implementing retail-led regeneration is doubted, as the research delivers mixed results. However the research indicates that the strategic benefits of restructuring and marketing the city have become equally if of not more important in retail-led regeneration initiatives than the actual economic benefits for the local economic community.
Keywords: 330